2020
DOI: 10.4102/hts.v76i2.5477
|View full text |Cite
|
Sign up to set email alerts
|

Performing the sacred – Aspects of singing and contextualisation in South Africa

Abstract: After an introduction and views on inculturation (i.e. adapting the liturgy to the context within which it is ‘performed’ or the context influencing the liturgy), the focus shifts to ‘incarnation’ and ‘contextualisation’ in a broader sense, to also include the transformation and adaptation of the ‘sacred’ for the secular or political sphere. Practices of performing faith through texts and music within diverse liturgical, spiritual, cultural and political contexts in South Africa are discussed. Aspects taken in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…Consistent with the previous studies (Kloppers 2020;Ngema 2020), the findings of this study reveal that singing an incomplete hymn eradicates the original meaning and purpose of the hymn. The researcher found that although contemporary gospel musicians are inspired by Zulu traditional hymns iCilongo Levangeli, the musicians must examine the context to understand the hymns.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with the previous studies (Kloppers 2020;Ngema 2020), the findings of this study reveal that singing an incomplete hymn eradicates the original meaning and purpose of the hymn. The researcher found that although contemporary gospel musicians are inspired by Zulu traditional hymns iCilongo Levangeli, the musicians must examine the context to understand the hymns.…”
Section: Discussionsupporting
confidence: 92%
“…This finding regarding the context of the composition of the hymns is in line with cognitive hermeneutics theory that promotes the importance of interpreting the text in its original language and within its historical context, artistic and aesthetic experiences and practical life (George 2020;Tönsing 2017). This finding corroborated the results of Osei-Bonsu (2013) and Kloppers (2020). The researchers found that understanding and singing hymns from the composers' perspective are essential because hymns are devoted to God and dedicated to the Supreme Being.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations